2013
DOI: 10.1136/tobaccocontrol-2013-051244
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette trafficking in five northeastern US cities

Abstract: Reducing cigarette trafficking would increase the effectiveness of tobacco taxes in reducing smoking and generate additional tax revenue, particularly in higher-taxed cities. Federal action to reduce cigarette trafficking, such as a track-and-trace system, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 18 publications
1
22
1
Order By: Relevance
“…Although we are not able to generalize these findings to the greater New York City region, the trends we observed were similar to those reported by Davis et al 20 They compared the findings of their 2011 littered pack survey conducted in New York City with the results of a similar littered pack study carried out by Chernick and Merriman in 2008 and 2009. 18 Davis et al found that the proportion of untaxed cigarettes was considerably lower in 2011 and that cigarette packs from Virginia had become the most prevalent nonlocal stamp in New York City, essentially documenting the same patterns we observed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although we are not able to generalize these findings to the greater New York City region, the trends we observed were similar to those reported by Davis et al 20 They compared the findings of their 2011 littered pack survey conducted in New York City with the results of a similar littered pack study carried out by Chernick and Merriman in 2008 and 2009. 18 Davis et al found that the proportion of untaxed cigarettes was considerably lower in 2011 and that cigarette packs from Virginia had become the most prevalent nonlocal stamp in New York City, essentially documenting the same patterns we observed.…”
Section: Discussionsupporting
confidence: 89%
“…In accord with past littered pack studies, 17,18,20,21 we weighted the proportions of each tax stamp category by the inverse number of packs found in each census tract to represent the South Bronx population. This measure weighted all of the census tracts equally.…”
Section: Littered Pack Surveymentioning
confidence: 99%
“…However, they do find considerable variability across countries, with little evidence of illicit packs in Portugal, Austria, Greece, Italy and Finland (all below 2%), with more significant shares in Bulgaria (18.3%), Sweden (18.8%), and Latvia (37.8%). Davis and colleagues, using estimates based on littered cigarette pack collections, conclude that illicit trade is a significant problem in four of the five cities in the north-eastern USA they examined 8. They find little evidence of illicit cigarettes in Philadelphia, while finding high levels of cigarette trafficking in Boston, New York, Providence, and Washington DC—up to 38.4%, 49.9%, 55.4%, and 59.9%, respectively.…”
Section: Measuring Illicit Tradementioning
confidence: 99%
“…Another study conducted face‐to‐face surveys where smokers were asked to provide information on their most recently purchased pack, including price 17. Studies examining littered cigarette packs have been used in many contexts to estimate the amount of tax avoidance and evasion; however, these studies are unable to determine what price was paid for these packs 18, 19, 20, 21.…”
Section: Introductionmentioning
confidence: 99%